Thermophysical analysis of time-dependent magnetized Casson hybrid nanofluid flow (Cu + GO/Kerosene Oil) using Darcy-Forchheimer and thermal radiative models for industrial cooling applications - Amal F. Alharbi; Fida Mohammad; Muhammad Usman; Naseem Khan; Walid Abushiba (Scientific Reports)
Abstract This paper presents an in-depth analytical investigation into the time-dependent flow of a Casson hybrid nanofluid over a radially stretching sheet. The study introduces the effects of magnetic fields and thermal radiation, along with velocity and thermal slip, to model real-world systems for enhancing heat transfer in critical industrial applications. The hybrid nanofluid consists of three nanoparticles—Copper and Graphene Oxide—suspended in Kerosene Oil, selected for their stable and superior thermal properties. The theory of Darcy-Forchheimer, along with the suction and injection effect, is applied to refine the flow behaviour and enhance heat transfer efficiency. The governing nonlinear equations are solved using the Homotopy Analysis Method to provide a robust framework for solution accuracy. The graphical and tabulated results demonstrated that hybrid nanofluid outperforms mono and Casson hybrid nanofluids. The result shows that, at a nanoparticle volume concentration of 0.03, the Casson hybrid nanofluid showed a remarkable 19.99% increase in heat transfer, compared to 14.80% for simple nanofluid. The magnetic parameter and thermal radiation parameter further amplify thermal conductivity. This research provided a critical insight into optimizing thermal management systems for advanced engineering applications, positioning hybrid nanofluid as highly effective solutions for next-generation cooling technologies.